Statistical Study of the Average Life Expectancy of The Population in Russia ("Journal "U". Economy. Management. Finance.", 2020)
The relevance of the research topic lies in the need to study the factor of life expectancy as one of the criteria showing the effectiveness of transformations in the social sphere. The work studied the indicator - the average life expectancy of the population for 2009 - 2019. Factors that reduce life expectancy are considered. Measures are proposed to increase the average life expectancy of the population. A factor analysis of life expectancy in the Russian Federation was carried out and a regression model was constructed.
Keywords: life expectancy; birth rate; mortality; demography; population density; economic factors